A model of small airship's propelling - Adamek, M. (2015)
For the purposes of development of a small and autonomously operated airship, a need to create a model of its propelling and motion has arisen. Being described within this paper, the model defines the requirements that are imposed to motors, propellers and the airship's controlling system. The model is based on a typical design of a small airship, that consists of two main propellers, being placed symetrically according to the gondola beneath the airship's bladder, and one tail propeller that is placed transversely at the airship's tail. According to this model, forces needed to move the airship in the desired direction can be estimated as well as the power consumption of the motors and angular velocity of the propellers. Although the dynamic model of the airship would exceed the framework of this paper, it is also described in broad terms and the results of two main simulations are presented hereby. The simulations describe the behavior of the airship in case of forward acceleration and braking as well as in case of yawing with such braking that ensures reaching of the desired yawing angle.